Pengaruh Brand Awareness, Online Consumer Review Dan Live Stream Terhadap Keputusan Pembelian Produk Skincare “Somethinc” Di Shopee : (Studi Pada Pengikut Akun Resmi “Somethinc” Di Aplikasi X) - Nurhaliza, Siti; Woelandari, Dewi Sri; Puspitorini, Ferawaty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
In the digital age, brand awareness is built not only through traditional advertising, but also through active interaction, online reviews, and social media content. This study aims to analyze the influence of brand awareness, online consumer reviews, and live streaming on the purchase decision of Somethinc skincare products on the Shopee platform, focusing on followers of the official Somethinc account on Application X. The research method used is quantitative, employing purposive sampling by distributing questionnaires to 100 respondents who are followers of the official Somethinc account on Application X. The analysis results show that the brand awareness variable does not have a significant effect on purchase decisions. In contrast, the variables of online consumer reviews and live streaming are proven to have a significant influence on purchase decisions.